2020
DOI: 10.1155/2020/8861004
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy for Gait, Balance, and Cognition in Individuals with Cognitive Impairment: A Retrospective Analysis

Abstract: Objectives. The purpose of this study was to determine if a pragmatic physical therapy (PT) program was associated with improved cognition, gait, and balance in individuals with cognitive impairment. This study investigated these associations for individuals with Alzheimer disease (AD), vascular dementia (VaD), dementia with Lewy bodies (DLB), and mild cognitive impairment (MCI) in order to better characterize outcomes to PT for each diagnostic group. Methods. Data before and after one month of physical therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Primary outcomes mainly used to evaluate the efficacy of physical therapies were balance, gait, and cognitive performance (Table 2). Significant improvements in all motor measures were found in a recent retrospective study in which 35 DLB participants underwent a 4-week structured PT programme in a clinical setting [17]. In a randomized controlled trial [18], involving a large cohort of persons with dementia, the following measures relative to 4 PDD participants were reported separately: after 12 weeks of intensive strengthening and balance exercises, 2 PDD assigned to the exercise group improved sit-to-stand, balance, and speed measures compared to the 2 PDD assigned to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary outcomes mainly used to evaluate the efficacy of physical therapies were balance, gait, and cognitive performance (Table 2). Significant improvements in all motor measures were found in a recent retrospective study in which 35 DLB participants underwent a 4-week structured PT programme in a clinical setting [17]. In a randomized controlled trial [18], involving a large cohort of persons with dementia, the following measures relative to 4 PDD participants were reported separately: after 12 weeks of intensive strengthening and balance exercises, 2 PDD assigned to the exercise group improved sit-to-stand, balance, and speed measures compared to the 2 PDD assigned to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic search identified five studies with LBD patients that underwent exercise training. The rehabilitation programme was generally an intensive aerobic exercise training of the duration of several weeks (from 4 to 12 weeks) with the specific aim of improving gait and balance [17][18][19] or executive functions [20]. Four of these studies reported positive effects of exercises as regards balance, gait measures [17][18][19], and executive functions measured through the Montreal Cognitive Assessment test [20].…”
Section: Physical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…WKS is treated with cognitive rehabilitation and thiamine replacement therapy, which has no set dosage and can vary depending on patients' symptoms. Physiotherapy can be used as a primary goal for managing primary treatment strategy in subjects with vascular dementia and dementia with Lewy bodies is needed to demonstrate the efficacy among these populations with the help of gait, balance, and cognitive therapy [ 19 ]. Combining dual-task and function-oriented challenges while controlling balance stimulates the sensory and neuromuscular control mechanisms.…”
Section: Discussionmentioning
confidence: 99%